Mechanism for Handling Violations of Campaign Materials by Bawaslu Bantul, Indonesia, in 2024 Pilkada - Putri, Shendy Eka; Sulaksono, Tunjung (Universitas Muhammadiyah Yogyakarta, 2026)
This study aimed to analyze the mechanism for handling violations of Campaign Tools (Alat Peraga Campaign/APK) carried out by the Bantul Election Supervisory Body (Bawaslu) during the 2024 Local Election, as well as to examine the inter-agency coordination established in the enforcement process. The analysis is framed within inter-institutional coordination theory and existing regulations, while also examining the inter-agency coordination established during the enforcement process and the factors influencing violation handling. This research employed a descriptive qualitative approach, with data collected through in-depth interviews with officials of Bawaslu Bantul, observations at the Bawaslu Bantul Office, and documentation related to violation records, plenary processes, and the implementation of APK removal. The findings indicated that violation handling was conducted through two main stages, namely prevention and enforcement. The prevention stage consisted of issuing corrective recommendations to election participants. In contrast, the enforcement stage proceeded through the registration of findings, preliminary review, advanced assessment, plenary meetings, issuance of recommendations to the Regional General Election Commission (KPU), and coordinated field removal involving the Civil Service Police Unit (Satpol PP). Bantul Regency recorded the highest number of APK violations in the Special Region of Yogyakarta, totaling 207 cases, requiring more intensive monitoring. The study revealed that successful enforcement was strongly influenced by inter-agency coordination involving Bawaslu, KPU, Satpol PP, Kesbangpol, the Environmental Agency (DLH), and security apparatus. This research contributes to strengthening the understanding of coordination-based violation-handling practices and highlights their importance in improving the quality of electoral oversight governance at the regional level.